2011
DOI: 10.1007/s11999-010-1568-1
|View full text |Cite
|
Sign up to set email alerts
|

High Complication Rate With Anterior Total Hip Arthroplasties on a Fracture Table

Abstract: Level IV, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
169
5
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(186 citation statements)
references
References 18 publications
5
169
5
2
Order By: Relevance
“…Spaans et al [6] reported also a high complication rate in the early experience of DAA THA, with no benefit shown when compared with the posterior approach. High complication rates were also reported by Jewett et al [5] who shown intra-operative complications in 26 out of 800 patients including trochanteric fractures (2.3 %) and femoral perforation (0.37 %). These two complications are related in our experience to either a coxa vara morphotype or a high anterior curvature of the proximal femur that requires a more important posterolateral release that may be difficult to achieve, especially in the early experience.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Spaans et al [6] reported also a high complication rate in the early experience of DAA THA, with no benefit shown when compared with the posterior approach. High complication rates were also reported by Jewett et al [5] who shown intra-operative complications in 26 out of 800 patients including trochanteric fractures (2.3 %) and femoral perforation (0.37 %). These two complications are related in our experience to either a coxa vara morphotype or a high anterior curvature of the proximal femur that requires a more important posterolateral release that may be difficult to achieve, especially in the early experience.…”
Section: Discussionsupporting
confidence: 51%
“…However, this cohort included his learning curve, suggesting that 3D planning may help decrease the intra-operative complication rate in the early experience of DAA. Indeed, with respect to the intra-operative complications, the learning curve varies according to the authors from 20 [18] to 200 [1,5]. In our future work, we will replicate this study with a variety of surgeons with different skill levels.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Numerous authors have reported low dislocation rates and rapid early functional recovery [1,29,31,33,36,40,46] with this approach. However, some studies have shown higher surgical blood loss and complication rates [6,47], particularly for less-experienced surgeons [16,43] or for patients who are obese [39]. Additionally, the distal extension of the approach is less familiar to most surgeons and a recent anatomic study by Grob et al [10] suggested that it may pose a risk to the neurovascular supply to portions of the vastus lateralis.…”
Section: Introductionmentioning
confidence: 99%
“…The anterolateral (AL), or Rottinger, approach, as with the DL approach, allows for maintenance of posterior capsular attachments and short external rotators, which reduces postoperative instability while maintaining abductor integrity [10][11][12]. However, anterior approaches to the hip, possibly including the AL approach, have been associated with increased rates of lateral femoral cutaneous nerve injury [13] and fractures of the greater trochanter and femur [14,15].…”
Section: Introductionmentioning
confidence: 99%